Diffusion-weighted MR Imaging After Angioplasty or Angioplasty Plus Stenting of Arteries Supplying the Brain - Jaeger, Horst J.; Mathias, Klaus D.; Drescher, Robert; Hauth, Elke; Bockisch, Georg; Demirel, Eren; Martin Gissler, Hans (American Journal of Neuroradiology, 2001)
BACKGROUND AND PURPOSE: There has been concern regarding the safety of revascularization procedures of vessels supplying the brain vessels because of the risk of cerebral embolization during the procedure. We have observed a high incidence of hyperintense lesions on diffusion-weighted MR images of the brain after stenting at the carotid bifurcation. The hypothesis of this study is that diffusion-weighted MR imaging of the brain can reveal new diffusion abnormalities after angioplasty or angioplasty plus stenting of arteries supplying the brain, other than at the carotid bifurcation. Therefore, we prospectively obtained diffusion-weighted MR images of the brain before and after such revascularization procedures.METHODS: Thirty-seven revascularization procedures were performed in 32 patients. Eleven interventions were performed at the distal internal carotid artery, two at the external carotid artery, two at the common carotid artery, five at the innominate artery, five at the vertebral artery, and 12 at the proximal subclavian artery. Diffusion-weighted MR imaging of the brain was performed before and 24 hours after the procedures.RESULTS: After eight (22%) of 37 procedures, new hyperintensities were visible on the diffusion-weighted MR images. With six of these eight procedures, the hyperintensities occurred in the vascular territory supplied by the treated vessel. In total, 35 new cerebral lesions could be seen, 33 (94%) of which occurred in the vascular territory supplied by the treated vessel. None of the patients in whom new diffusion abnormalities were found had new neurologic symptoms or deficits. No new lesions could be seen after procedures at the subclavian artery.CONCLUSION: Revascularization procedures of arteries supplying the brain were associated with new lesions on the diffusion-weighted MR images of the brain after 22% of the procedures, provided that MR imaging could be performed, indicating the occurrence of cerebral microemboli during such procedures. Diffusion-weighted MR imaging of the brain can be used as a tool to assess the impact of modifications of procedural technique and/or the use of cerebral protection devices on the occurrence of such lesions.